Review on energy management system in microgrids - Nor Su’aida, Yusof; Abu Zaharin, Ahmad (2022)
Microgrid has been widely used as an approach for the integration of distributed energy sources with energy storage systems in the electrical distribution network. It is developed as a building block for the smart grid system. In this paper, the review focuses on a comparative controller in a microgrid for energy management systems (EMS) is presented. The EMS is crucial in microgrid operation as it is used to control the power flow to the load demands and voltage sharing due to uncertainties of the input energy sources. As an outcome, the review provided the researcher with viewing the existing approaches and possibilities for improvement.